HEART REMODELING IN OVERWEIGHT AND OBESITY WITH CARDIAC COMORBIDITIES - I. V. Logacheva; T. A. Ryazanova; V. R. Makarova; F. R. Avzalova; N. I. Maksimov (Российский кардиологический журнал)
Aim. To assess structural geometric and functional disorders of the heart in males with coronary heart disease (CHD) comorbid with arterial hypertension (AH) and with visceral abdominal obesity, and to evaluate the grade of association of epicardial fat thickness (EFT) with cardiometabolic risk factors (RF).Material and methods. Totally, 90 in-patients included, males with AH and CHD and with metabolically unhealthy phenotype (MUP) at the age 61,2±1,7 y. o. with normal bodyweight (n=29) — 1 group, overweight (n=21) — 2 group, and obese (n=30) — 3 group, and 30 persons with metabolically healthy phenotype. All patients underwent anthropometric screening, calculation of visceral obesity index (VAI) and insulin resistance (HOMA-IR); lipid profile was assessed, and by the data from echocardiography the myocardial mas index (MMI) was evaluated, and EFT, the characteristics of the left ventricle hypertrophy (LVH) were counted and of diastolic dysfunction (DD).Results. The presence of obesity led to increase of metabolic RF in obese patients. Most informative were indexes as VAI (4,47±0,27; p<0,001) and НОМА-IR (5,12±0,32; p<0,001). In obese patients there was association of MMI and EFT (r=0,81, p<0,001), predominance of concentric LVH with formation of restrictive DD. Regardless the level of abdominal obesity, there was increase of EFT in MUP patients, and the relation was confirmed to the main metabolic RF, as with structural geometric parameters of the heart.Conclusion. Cardiological patients with AH and CHD in MUP had increased levels of markers of anomalous phenotype, the values increased with obesity. In obese patinents (groups II, III) as a predominant trend there was concentric LVH, restrictive DD, significant increase of preload and left atrium volume. The significance of EFT was confirmed as a marker of visceral obesity. Study results show that obesity in comorbidity patients with cardiac pathology does influence the increase of cardiometabolic RF, worsens the remodeling of the heart and negatively influences cardiac muscle function.